Políticas Industriais Recentes no Brasil: retomada e limites - Santana, Victor Hugo Tabarez (Universidade do Vale do Rio dos Sinos, 2018)
Since its emergence Industrialization has played a relevant role for national economies as a strenghtening factor and later as a propitiator of qualified jobs, making the production base more complex and providing material well-being. Industrial policies received much attention in the post-Second World War and then received less emphasis under the heydey of the neoliberal thinking after 1980. However, several Asian economies persisted in a trajectory of connexion between state and private markets, resulting in satisfactory outcomes in several economic aspects. Studies on industrial policies have been carried out by several researchers in different institutions of developed countries in the 21st century. In Brazil, industrial policies played a major role throughout the period of industrialization and lost their prominence after the 80s. They came to light once again in the period of 2003 - 2014, with three major programs launched in 2004, 2008 and 2011. In assessing the goals mentioned in these programs related to the exports performance, the results obtained at the end of 2014 are below the target, signaling that the success of these initiatives depends on the combination of several elements, through which a national development project can be affirmed, in a context of great transformations through which economies that are at the forefront of economic development pass in the current era.
Keywords: Industrialização; Estado; Política industrial; Exportações; Resultados; Industrialization; State; Industrial policy; Exports; Results; ACCNPQ::Ciências Sociais Aplicadas::Economia